2022
DOI: 10.1038/s41467-022-35527-4
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog-mediated gut-taste neuron axis controls sweet perception in Drosophila

Abstract: Dietary composition affects food preference in animals. High sugar intake suppresses sweet sensation from insects to humans, but the molecular basis of this suppression is largely unknown. Here, we reveal that sugar intake in Drosophila induces the gut to express and secrete Hedgehog (Hh) into the circulation. We show that the midgut secreted Hh localize to taste sensilla and suppresses sweet sensation, perception, and preference. We further find that the midgut Hh inhibits Hh signalling in the sweet taste neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 69 publications
2
15
0
Order By: Relevance
“…Taken together with previous studies testing proboscis extension, 17, 39 these results suggest that excess dietary sugar globally dampens short-term behavioral responses to sugar. Because we used optogenetic stimulation of sugar neurons, which bypasses sugar receptor activation, our results additionally demonstrate that a high-sugar diet decreases sugar sensitivity by acting downstream of the sugar receptors.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Taken together with previous studies testing proboscis extension, 17, 39 these results suggest that excess dietary sugar globally dampens short-term behavioral responses to sugar. Because we used optogenetic stimulation of sugar neurons, which bypasses sugar receptor activation, our results additionally demonstrate that a high-sugar diet decreases sugar sensitivity by acting downstream of the sugar receptors.…”
Section: Resultssupporting
confidence: 83%
“…A high-sugar diet reduces proboscis extension to sugar but leads to increased long-term feeding. 15,17,39 We found that a high-sugar diet reduces other behavioral responses to sugar, suggesting that short-term responses to sugar are globally dampened. How and where does this suppression occur?…”
Section: Effects Of a High-sugar Diet On Sweet Taste Processingmentioning
confidence: 79%
See 1 more Smart Citation
“…Knockdown of Hh signaling leads to elevated levels of triglycerides in the D. melanogaster fat body (16, 17, 43), and canonical Hh signaling in the fat body activates the Ci transcription factor increasing the expression of the lipase encoding gene bmm (18). In D. melanogaster adults, Hh signaling from midgut ECs to the taste sensilla regulates sweet sensation and perception (44). In mouse activation of the Hh pathway in the adipocyte lineage suppresses high fat diet induced obesity (45) and signals through Gαi, extracellular Ca ++ , and Amp kinase to induce a Warburg-like shift in metabolism (26).…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining was performed as previously reported (Zhao et al, 2022) with minor changes. Flies were briefly rinsed in 95% ethanol and dissected in 1xPBS at room temperature.…”
Section: Methodsmentioning
confidence: 99%